PSYCHOLOGICAL WELL-BEING AND WORK-LIFE BALANCE FOR WOMAN LECTURERS - Yudiani, Ema; Istiningtyas, Listya (Psikis : Jurnal Psikologi Islami, 2022)
This study aims to determine the relationship between Psychological Well-Being by reviewing Work-Life Balance for women lecturers at UIN Raden Fatah Palembang. This research used quantitative correlational research. The population in this study was 225 female lecturers at UIN Raden Fatah Palembang. This study used a purposive sampling technique with the criteria of being married, having children, and willing to be the research subject. The sample was 54 female lecturers at UIN Raden Fatah Palembang. The scale used in this study is the Work-Life Balance Scale and the Psychological Well-Being Scale, which are adjusted and adapted based on the theory. This study used simple regression analysis techniques using the Statistical Program for Social Science (SPSS) version 23.0 for windows. The results of the R square test for the Work-Life Balance variable on Psychological Well-Being are 0.081. These results indicate that 8.1% of the variable Psychological Well-Being is influenced by Work-Life Balance, while other factors outside Work-Life Balance influence the rest. From the data on the categorization of Work-Life Balance variables and Psychological Well-Being variables, it is known that the subject is still in the low to medium category.